2018
DOI: 10.7150/jca.22418
|View full text |Cite
|
Sign up to set email alerts
|

Paired box 2 promotes progression of endometrial cancer via regulating cell cycle pathway

Abstract: Background: Human paired box 2 (PAX2) plays a key role in cell fate, early patterning and organogenesis.Methods: We investigated the function of PAX2 on the biological behavior of endometrial cancer in vitro and in vivo and to explore the regulation mechanism, stable knocking-down and over-expression PAX2 endometrial cancer cell lines were established. CCK-8 and transwell assays were applied to determine proliferation, invasion and migration ability. Cell cycle distribution was analyzed by flow cytometry. Affy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In this study, four cases (two hyperplasia without atypia and two proliferative endometrium) were diagnosed by using ZW-FA as potentially precancerous or malignant lesions. As Senol et al reported previously, 29.4% of endometrial hyperplasia was found with FR-α expression and 6.7% was found with high FR-α expression, and endometrial cancer was found with signi cantly high FR-α expression [33]. Consistently in this study, signi cantly higher FR-α expression was encountered in endometrial carcinomas in comparison to hyperplasia and normal endometrium.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, four cases (two hyperplasia without atypia and two proliferative endometrium) were diagnosed by using ZW-FA as potentially precancerous or malignant lesions. As Senol et al reported previously, 29.4% of endometrial hyperplasia was found with FR-α expression and 6.7% was found with high FR-α expression, and endometrial cancer was found with signi cantly high FR-α expression [33]. Consistently in this study, signi cantly higher FR-α expression was encountered in endometrial carcinomas in comparison to hyperplasia and normal endometrium.…”
Section: Discussionsupporting
confidence: 90%
“…At present, there are few studies regarding the role of CCNB1, CCNB2, and CCNA2 in EC. Wang J. et al, 2018 found that CCNA2 expression was high and was positively correlated with histological grades, where a higher expression of CCNA2 was associated with worse differentiation in endometrial adenocarcinoma. CDK1 is a target gene of miR-1271, human paired box 2 and LncRNA ABHD11-AS1 and regulates endometrial carcinoma cell line proliferation, invasion, migration, apoptosis, and other mobility factors (Li et al, 2017; Liu Y. et al, 2018; Wang J. et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Wang J. et al, 2018 found that CCNA2 expression was high and was positively correlated with histological grades, where a higher expression of CCNA2 was associated with worse differentiation in endometrial adenocarcinoma. CDK1 is a target gene of miR-1271, human paired box 2 and LncRNA ABHD11-AS1 and regulates endometrial carcinoma cell line proliferation, invasion, migration, apoptosis, and other mobility factors (Li et al, 2017; Liu Y. et al, 2018; Wang J. et al, 2018). In vulvar squamous cell carcinoma, elevated levels of CDK1 were found in patients with advanced tumor behaviors and aggressive features (Wang Z. et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…The Rac1 pathway is closely associated with the invasion and metastasis of ES; a previous study has demonstrated that Erb-B2 receptor tyrosine kinase 4 mediates Rac1 GTPase activation and enhances ES invasion and metastasis in vivo by activating the PI3K-Akt cascade and focal adhesion kinase (40). The cell cycle pathway serves a key role in the malignant proliferation process in breast (41), endometrial (42), bladder (43) and gastric (44) cancer. A recent study reported that the cell cycle pathway is also involved in the ES proliferation process (45).…”
Section: Discussionmentioning
confidence: 99%